Growth hormone and body composition in athletes - Frisch, H. (Journal of Endocrinological Investigation, 1999)
The anabolic properties of growth hormone (GH) have been investigated extensively. The effects of GH on normal, hypertrophied and atrophied muscles have been studied previously in animal experiments that demonstrated an increase in muscle weight and size, but no comparable increase in performance or tension. In adults with GH deficiency, the changes in body composition can be corrected by GH treatment; lean body mass and strength increase within a few months. In children with GH deficiency, Turner's syndrome or intrauterine growth retardation, an increase in muscle tissue is seen after treatment with GH. In acromegalics with long-standing GH hypersecretion, the muscle volume is increased, but muscle strength and performance are not improved. These observations gave rise to the interest shown by healthy subjects and athletes in using GH to increase their muscle mass and strength. The improvements in muscle strength obtained by resistance exercise training in healthy older men or young men were not enhanced by additional administration of GH. The larger increases in fat-free mass observed in the GH-treated groups were obviously not due to accretion of contractile protein, but rather to fluid retention or accumulation of connective tissue. In experienced weightlifters, the incorporation of amino acids into skeletal muscle protein was not increased and the rate of whole body protein breakdown was not decreased by short-term administration of GH. The results of a study in power athletes confirm the results of these investigations. The study used GH treatment in power athletes compared with a placebo-control group, and the results indicated no increase in maximal strength during concentric contraction of the biceps and quadriceps muscles, although levels of insulin-like growth factor-I were doubled. In highly trained power athletes with low fat mass and high lean body mass, no additional effect of GH treatment on strength is to be expected.